A interdisciplinaridade em diferentes contextos educacionais: contribuições para o ensino de biologia - Nicoletti, Elenize Rangel (2017)
The present work investigated how the interdisciplinarity is present in different contexts of Biology teaching. This research used a quanti-qualitative approach, through documentary analysis, semi-structured questionnaires and interventions. Initially, questions about the National High School Examination Virus (ENEM) were analyzed from 1998 to 2014 to identify how interdisciplinary and contextualisation were present. A total of 473 high school students (MS) and 43 Biology professors from 17 schools from different municipalities of Rio Grande do Sul (RS) participated in the study, in addition to 79 undergraduate students in Biological Sciences from three institutions. Higher Education of the RS. Also, students and teachers of an EJA class from a state school in the central region of RS and a group of Basic Education teachers participating in a continuing education course from another state school in the northwest RS region were research subjects. The analysis of the ENEM evidence pointed out that the contextualization and interdisciplinarity, although present in the questions, is not required for resolution. Research with MS students and teachers has shown that there are different interests between the two groups. While the former wants to learn current topics that allow relationships between biology and other areas of knowledge (languages, mathematics, humanities and natural sciences), biology teachers prioritize in their classes what is in the textbook. When compared to Biology graduates, Biology teachers demonstrated greater difficulty in selecting content from the Virus theme of an initial listing. However, teachers have a greater ability to relate subjects to different areas of knowledge than to undergraduates. The implementation of the Islands of Rationality methodology in the EJA encouraged the protagonism and criticality of the students. The evaluation of a methodology that assists in the organization of interdisciplinary activities, based on the construction of Relational Schemas, has shown to have a good potential during the short course given to a group of Basic Education teachers. It is hoped that the results of this set of investigations will subsidize, in addition to new research, new perspectives on the teaching of biology, contributing to the knowledge being seen in a less fragmented way.